Analisis Pemanfaatan Teknologi dalam Meningkatkan Mutu Pembelajaran di Lembaga Pendidikan Islam - Sariyah Sariyah; Mario Mario; Selnistia Hidayani (CV. Lentera Literasi Indonesia, 2026)
The development of information and communication technology has driven significant transformations in learning practices, including in Islamic educational institutions that have distinctive values and cultural characteristics. This study aims to examine the concept of educational technology utilization, analyze the quality of learning in Islamic educational institutions, and examine the effectiveness of educational technology in improving the quality of learning while remaining based on Islamic educational principles. The research method used is library research with a descriptive qualitative approach through analysis of books, national and international scientific journal articles, and other relevant documents. The results of the study show that the use of educational technology, which includes aspects of learning design, utilization, management, and assessment, can improve the effectiveness of learning, learning motivation, cognitive involvement of students, and the quality of academic services. However, its implementation still faces various challenges, such as infrastructure limitations, low technological competence of educators, resistance to change, and lack of managerial support. The novelty of this research lies in the analysis of the use of educational technology as a strategy to improve the quality of learning that is integrated with Islamic values and relevant to the perspective of educational psychology, particularly in the aspects of motivation, learning interaction, and learning experience.